Is Decellularized Porcine Small Intestine Sub-mucosa Patch Suitable for Aortic Arch Repair? - Corno, Antonio F.; Smith, Paul; Bezuska, Laurynas; Mimic, Branko (Frontiers in Pediatrics, 2018)
Introduction. We reviewed our experience with decellularized porcine small intestine sub-mucosa (DPSIS) patch, recently introduced for congenital heart defects. Materials and Methods. Between 10/2011 and 04/2016 a DPSIS patch was used in 51 patients, median age 1.1months (5days-14.5 years), for aortic arch reconstruction (45/51=88.2%) or aortic coarctation repair (6/51=11.8%). All medical records were retrospectively reviewed, with primary endpoints interventional procedure (balloon dilatation) or surgery (DPSIS patch replacement) due to patch-related complications. Results. In a median follow-up time of 1.5±1.1years (0.6-2.3years) in 13/51 patients (25.5%) a re-intervention, percutaneous interventional procedure (5/51=9.8%) or re-operation (8/51=15.7%) was required because of obstruction in the correspondence of the DPSIS patch used to enlarge the aortic arch/isthmus, with median max velocity flow at Doppler interrogation of 4.0±0.51m/sec. Two patients required surgery after failed interventional cardiology. The mean interval between DPSIS patch implantation and re-intervention (percutaneous procedure or re-operation) was 6months (1-17months). While there were 3 hospital deaths (3/51=5.9%) not related to the patch implantation, no early or late mortality occurred for the subsequent procedure required for DPSIS patch interventional cardiology or surgery. The median max velocity flow at Doppler interrogation through the aortic arch/isthmus for the patients who did not require interventional procedure or surgery was 1.7±0.57m/sec. Conclusions. High incidence of re-interventions with DPSIS patch for aortic arch and/or coarctation forced us to use alternative materials (homografts and decellularized gluteraldehyde preserved bovine pericardial matrix).